The role of visual culture in reading the artwork among Students in the Department of Art Education (Journal of the College of Basic Education, 2022)
That artwork is the field of personal development of the learner from the expressive and creative and the acquisition of basic skills and techniques in the fields of fine arts as a tool does not give an idea of ​​the ability to understand other works of art, to make way for the learner to see the many works of art and various images See all what is an innovative and new in art allows the learner to use visual material is able to be converted into a wider and more comprehensive ideas, deeper and gives him a different vision of what watching or perceives or read by, and this is what happens through learning and visual perception based on the convergence theory of knowledge, technology, and this is what we call visual culture and this is what It represents the goal of research that seeks to establish (the researcher) a. Reading artistic production by the students of the Department of Art Education in the light of the visual cultureThe visual culture took a great interest by researchers and specialists in the fields of art, flags, especially in an era of technological revolution accelerated, the researcher is seeking, through her research to open new windows to read artistic output through visual culture and identify them and this is what the researcher is seeking to him through the goal search.Thus, researchers must in art and connoisseurs have read the image and depth out and think about where that visual culture is training through the eye and the mind as Richard Stern Richard Stern explained and Rhonda Robinson Rhonda Robinson is the process of cognition agent complex, effective and can promote and develop through the concepts of development the individual self and the ability to express and development accounting for the eyes, the ears and the brain, which represents members responsible for the visual and auditory perception system information is complex and this network receives signals resulting from the surrounding environment, whether electromagnetic way or the mechanical and converts it to a regular pulses of information cipher and then send it to the brain to be processed and then give meanings specified (Dwyer and Moore, T. Azmi, p 2.1915) and that what was done by a researcher at the research procedures when it took a sample of the paintings are (Abaddon), German artist (Max Ernst) and keyboard (the disintegration of the urgency of memory) of the artist (Salvador Dali) and two belong to the surrealist school and display two works on the students of the Department of art Education / College of Education and human Sciences / University of Tikrit, totaling (37 students) and provide them with form for the analysis of the work of art, and after extracting the statistics by building analysis form which has been obtaining the virtual her honesty by offering a set of experts who have helped out and finalized after obtaining the search tool to remain steadfast by professionals in this area was reached in accordance with the objectives of the research results, which stipulates results Through analysis form designed by the researcher and display sample (two works Professionals artist Max Ernst and Salvador Dali) and presented to the students of the Department of Art Education Phase III Department of Art Education, Faculty of Education and Human Sciences, University of Tikrit, after extracting the results researcher found that they achieved the goal of SearchRead the artistic production by the students of the Department of Art Educationthe effect of the role of visual culture, which plays an important role in understanding and analyzing the artistic production.3.tattabr visual culture an important element of the art students and through which art students can decode any work of art, whether sculpture, drawing, music or theater.Technical 4.alnteg is the set of elements or forms or symbols formed by a specialist in the art (the artist), who must have a visual culture can be achieved fantastic works of art;Through previous findings emerged promised to conclusions, including1.visual culture plays an important role at the student art and the artist.2.You must boil art students and art students to delve and interested in the study of visual culture.3.dialogue between visual culture and artistic production and art gives students a vision and a deep philosophical dimension.5.requires the recipient to have a taster of art, cultural and technical reference and sham qualify it to play its role as an analyst and translator of the work of art.In light of the above findings and conclusions of the researcher recommends the following;1.drash visual culture on a large scale by the faculties of Fine Arts students2.annexation of visual culture into the school curriculum in the colleges of Arts.The researcher also presented a set of proposals, including1.qrah visual culture in accordance with the educational and technical data.2.ttaiwir studies on the works of art or artistic production, especially modern ones.